Thinking through and about anthropomorphic figurines. A cognitive and neuroarchaeological approach to the study of peak sanctuary practices - Anastasia Chrysanthi Solomou (Les Carnets de l’ACoSt)
One of the defining characteristics of Cretan peak sanctuaries are the clay anthropomorphic figurines, which are observable in large quantities on nearly all such sites, and which are seldom associated with other contexts. The exclusivity and omnipresence of these artefacts renders them one of the most suitable areas of research with a view to re-examining the practices and performances taking place on these sites. This study focuses on the clay anthropomorphic figurines, following a neuroarchaeological and cognitive approach, drawing on neurological studies regarding the function and neurological and mental sequalae of mirror neuron activation, as well as concepts of material engagement, and the use of the figurines as a form of shared exographic memory system. The figurines are thereby seen as vital active constituents of the cognitive processes taking place in these sites, facilitating and enhancing the cognitive preparation for –and participation in– the peak sanctuary performances. Through this approach, the role of these objects as part of a larger cognitive network, shared by the participants of the peak sanctuaries throughout Crete, is proposed, and the potential socio-political and economic significance of this role is highlighted.